Detection apparatus for be used for megawatt level wind generating set cantilever support spare - YANG HUI; XIAO JIECHANG; ZHOU YIPU; CHEN WEIYAO; XU FAN; WU SONGLU (2016)
The utility model discloses a detection apparatus for be used for megawatt level wind generating set cantilever support spare, including detecting base plate and a plurality of locating pin, a plurality of locating pins are vertical to be fixed in and to detect in order to form a plurality of detection area that are used for different specification cantilever support spares on the base plate, and a plurality of locating pins of every detection area all are used for inserting in the mounting hole of the cantilever support spare of corresponding specification to whether the trompil that detects cantilever support spare is accurate. The utility model has the advantages of simple structure is compact, the cost of manufacture low, convenient to use, detection efficiency are high, it is high to detect the precision. 本实用新型公开了种用于兆瓦级风力发电机组悬臂支撑件的检测装置，包括检测基板和多个定位销，多个定位销竖直固定于检测基板上以形成多个用于不同规格悬臂支撑件的检测区域，每个检测区域的多个定位销均用于插入对应规格的悬臂支撑件的安装孔内，以检测悬臂支撑件的开孔是否精准。本实用新型具有结构简单紧凑、制作成本低、使用方便、检测效率高、检测精度高的优点。